Cross-cultural and gender associations with anxiety about electronic data hacking. (May 2017) - Elhai, Jon D.; Chai, Sangmi; Amialchuk, Aliaksandr; Hall, Brian J.
Abstract: We investigated the impact of data hacking on clinical anxiety and worry. 389 American and 216 Korean college students were recruited, surveyed using the Generalized Anxiety Disorder-7 (GAD-7) questionnaire, and adapted GAD-7 specifically assessing data hacking anxiety. Using confirmatory factor analysis with measurement invariance testing, Koreans scored higher on severity of hacking anxiety items, and differently on factor loadings. Controlling for other variables such as age and prior hacking victimization, cultural group status remained a robust predictor for hacking anxiety. Hacking anxiety in both cultural groups was higher in women than men. Results are placed into the context of theory on information privacy concerns and cross-cultural differences on such concerns. Highlights: Koreans students evidenced greater anxiety about data hacking than Americans. Koreans evidenced greater anxiety about hacking than general anxiety. Women were higher on hacking anxiety than men.